1990
DOI: 10.1029/jb095ib08p12449
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurements of shear wave polarizations at the Anza Seismic Network, southern California: Implications for shear wave splitting and earthquake prediction

Abstract: We analyze shear wave polarizations from local earthquakes recorded by the Anza network in southern California, using an automated method which provides unbiased and quantitative measurements of the polarization and the duration of linear motion following the shear wave arrival (the linearity interval). Initial shear wave particle motions are strongly aligned at four stations, a feature that is not predicted by focal mechanisms. The particle motion alignment is most likely caused by shear wave splitting due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
124
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(128 citation statements)
references
References 58 publications
4
124
0
Order By: Relevance
“…However, for a laterally heterogeneous and anisotropic medium like the earth, the particle motion usually involves interference of direct, refracted, reflected, and scattered body and surface waves that are not constrained to a plane, resulting in complex polarization and energy transport off the great-circle. This complexity has motivated the development of sophisticated polarization analysis techniques to constrain the effects of heterogeneity and anisotropy on seismic wave propagation, including path deflection effects (e.g., BOOTH et al, 1991;CRAMPIN, 1970CRAMPIN, , 1975CRAMPIN et al, 1990CRAMPIN et al, , 1991KIRKWOOD and CRAMPIN, 1981;PARK et al, 1987;SILVER and CHAN 1988;VINNIK et al, 1989;LASKE and MASTERS, 1996;VIG and MITCHELL, 1990;ASTER et al, 1990ASTER et al, , 1991LEVSHIN et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, for a laterally heterogeneous and anisotropic medium like the earth, the particle motion usually involves interference of direct, refracted, reflected, and scattered body and surface waves that are not constrained to a plane, resulting in complex polarization and energy transport off the great-circle. This complexity has motivated the development of sophisticated polarization analysis techniques to constrain the effects of heterogeneity and anisotropy on seismic wave propagation, including path deflection effects (e.g., BOOTH et al, 1991;CRAMPIN, 1970CRAMPIN, , 1975CRAMPIN et al, 1990CRAMPIN et al, , 1991KIRKWOOD and CRAMPIN, 1981;PARK et al, 1987;SILVER and CHAN 1988;VINNIK et al, 1989;LASKE and MASTERS, 1996;VIG and MITCHELL, 1990;ASTER et al, 1990ASTER et al, , 1991LEVSHIN et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…There are no exceptions is repeated three times. But at least one published study argues for an exception (Aster et al 1990(Aster et al , 1991, and an earlier study by Ryall and Savage (1973) also presented some negative SWS results.…”
Section: Thomas H Jordan 1 and Lucile M Jonesmentioning
confidence: 94%
“…There are no exceptions is repeated three times. But at least one published study argues for an exception (Aster et al 1990(Aster et al , 1991, and an earlier study by Ryall and Savage (1973) also presented some negative SWS results.Crampin's (2010) representation of ideas as facts typifies an exclamatory style of argumentation that has all too often been employed by proponents of earthquake prediction schemes (see Geller 1997 for a critical review). A relevant critique was articulated by the International Commission on Earthquake Forecasting (ICEF) in its preliminary report (Jordan et al…”
mentioning
confidence: 94%
“…The dashed line is evaluated for the same stress history but for water at temperatures and pressures at a 10 km-depth, approximately halfway along the average ray path for these earthquakes suggested that this repeated activity with predictable precursors makes isolated swarms particularly important for investigating earthquake preparation zones .) (Note that the critical observations showing temporal changes in shear-wave splitting at Anza (Peacock et al, 1988; were not reproduced when Aster et al (1990) measured time delays between split shear-waves on the same data set with an automatic technique. showed that the automatic technique of Aster et al (1990) introduced factor-of-two errors into measurements of the time delays.…”
Section: Introductionmentioning
confidence: 99%
“…(Note that the critical observations showing temporal changes in shear-wave splitting at Anza (Peacock et al, 1988; were not reproduced when Aster et al (1990) measured time delays between split shear-waves on the same data set with an automatic technique. showed that the automatic technique of Aster et al (1990) introduced factor-of-two errors into measurements of the time delays. Since the whole measured variation only had a range of a factor of two (see Fig.…”
Section: Introductionmentioning
confidence: 99%